(Z)-Ethyl 2-hydroxyimino-2-(4-nitrobenzyl)ethanoate - Caracelli, Ignez [UNESP]; Trindade, Antonio C.; Moran, Paulo J. S.; Hinoue, Luciana; Zukerman-Schpector, Julio; Tiekink, Edward R. T. (Wiley-Blackwell, 2010)
The title molecule, C(11)H(10)N(2)O(6), has a Z conformation about the C = N bond of the oxime unit. There are significant twists from planarity throughout the molecule, the most significant being between the hydroxyimino and ester groups which are effectively orthogonal with an N-C-C-O(carbonyl) torsion angle of 91.4 (2)degrees. The crystal packing features oxime-benzoyl O-H center dot center dot center dot O contacts that lead to chains along [010] and C-H center dot center dot center dot O interactions also occur.